Public Health Issues And Observations Made During Meat Inspection At Bodija Municipal Abbatoir, Ibadan, Oyo State, Nigeria (2008)
the provision of wholesome meat for the public remains the pre-occupation of the veterinary public health practitioners through systematic examinations of food animals such as cattle,goats, sheep and pigs, before and after slaughter with a view to ascertaining whether they are infected by certain scheduled or zoonotic diseases (thorton,1968). therfore,the aim of meat inspection is to provide safe and wholesome meat for human consumption (herenda et al, 1994). several reports have been made on the prevalence rates of diseases of public health importance in Nigeria (babalola and Van Veen, 1976; Antia and Alonge, 1981;Nwosu,1987) and the abbatoirs in the country have continued to experience infrastructural decay and low quality staff leading to general breakdown in the thoroughness of meat inspection. cleaning and sanitation are always considered as important and integral part of the measures necessary to avaoid th transmission of zoonotic diseases (Alonge,2001). in most communities, meat has long occupied a special place in the diet, for a variety of reasons including taste preference, prestige,tradition and availability,with the nutritional aspects being included more recently 9Rogowski,1980). this study was therefore undertaken to assess the public health issues related to meat inspection and observed practices involved in meat processing at the Bodija Municipal Abbatoir. This is with a view to pointing out ways of improving the activities of the meat inspectors and processors in order to provide safe and whollesome meat for the public.